Aerosol hygroscopicity and visibility estimates in the Great Smoky Mountains National Park - Kreidenweis, Sonia M., author; Hand, Jenny L., author (Colorado State University. Libraries, 1997)
Summertime visibility in the National Parks in the Eastern United States is often very poor, due to high particulate mass concentrations and high relative humidities. As a part of the Southeastern Aerosol and Visibility Study (SEAVS) in the Great Smoky Mountains National Park during the summer of 1995, aerosol size distributions (Dp = 0.1-3 µm) were measured with an Active Scattering Aerosol Spectrometer (ASASP-X). A relative humidity (RH) controlled inlet allowed for both dry and humidified measurements. The objective of this experiment was to examine the aerosol size distribution and its variation with RH to characterize its effect on visibility in the region. The ASASP-X was calibrated with polystyrene latex spheres (PSL) (m = 1.588), however, the instrument response was sensitive to the refractive index of the measured particles, which was typically much lower than that of PSL. An inversion technique accounting for varying particle real refractive index was developed to invert ASASP-X data to particle size. Dry (RH < 15%) particle refractive indices were calculated using the partial molar refractive index method and 12-hour fine aerosol (<2.5 µm) chemical compositions from the National Park Service Interagency Monitoring of Protected Visual Environments (IMPROVE) filter samples. A study average dry refractive index of m = 1.49 ± 0.02 was determined. The dry aerosol number distributions inverted using the scaling method were fit with single mode lognormal curves, resulting in dry accumulation mode size parameters. A study average total volume concentration of 7 ± 5 µm3 cm-3 was determined, with a maximum value of 26 µm3 cm-3. The large variability was due to extremes in meteorological situations occurring during the study. The study average volume median diameter was 0.18 ± 0.03 µm, with an average geometric standard deviation of 1.45 ± 0.06. A newly-developed iteration method was used to determine wet refractive indices, wet accumulation mode volume concentrations and water mass concentrations as a function of relative humidity. Theoretical predictions of water mass concentrations were determined using a chemical equilibrium model assuming only ammonium and sulfate were hygroscopic. Comparisons of predicted and experimental water mass showed agreement within experimental uncertainties. To examine the effects of particles on visibility, particle light scattering coefficients, bsp, were calculated with derived size parameters, refractive index and Mie theory. Dry scattering agreed well with nephelometer measurements made at SEAVS, with an average bsp of 0.0406-km-1. Estimates of particle light scattering growth (b/b0) were determined from ratios of wet and dry light scattering coefficients, and also agreed with nephelometer results. The new inversion techniques were compared to earlier, simpler methods which ignored variations in aerosol chemical composition. The simpler method yielded smaller mean diameters, however, hygroscopicity estimates were comparable to those derived using daily varying chemical composition. This suggests that although the aerosol chemical composition is needed to determine aerosol size parameters, it may not be critical for deriving hygroscopicity (or other ratios of size parameters). This result may be specific to this study, as the variation in refractive index with RH assumed by previous models appears to be a good estimate for that observed during SEAVS.
National Park Service.
Keywords: southeastern aerosol and visibility study (SEAVS); Aerosols -- Measurements; Air -- Pollution -- Great Smoky Mountains National Park (N.C. and Tenn.)